Design of Computer-Based Paliative Nursing and Paliative Screening Documentation Information Systems - Mulyono Mulyono; Emilia Puspitasari Sugiyanto (GLOBAL HEALTH SCIENCE GROUP, 2023)
Documentation of nursing care is an important part of the nursing process, many methods have been developed to make it easier for nurses to carry out the nursing process. It is hoped that the documentation system developed will be able to facilitate the nurse's task. The palliative nursing documentation process is . special nursing documentation for palliative nursing which consists of assessment, formulation of diagnoses, interventions, implementation and evaluation. The documentation format for palliative nursing care includes a palliative screening assessment. This documentation system was developed in nursing education institutions to facilitate the learning process and provide students with direct experience in the application of the nursing care documentation system, especially palliative nursing. The purpose of this study was to design a computer-based palliative nursing care documentation system. This type of research is design research with expert system analysis. The research activity began with the creation of a diagram of the nursing care documentation process flow system. After the flowchart system is made, the researcher begins to design a system that is in accordance with the flowchart design. The results obtained are the design of the nursing care documentation system and palliative screening. The nursing documentation system can be used for learning palliative nursing care and screening paiative patients using screening. The research activity began with the creation of a diagram of the nursing care documentation process flow system. After the flowchart system is made, the researcher begins to design a system that is in accordance with the flowchart design. The results obtained are the design of the nursing care documentation system and palliative screening. The nursing documentation system can be used for learning palliative nursing care and screening paiative patients using screening. The research activity began with the creation of a diagram of the nursing care documentation process flow system. After the flowchart system is made, the researcher begins to design a system that is in accordance with the flowchart design. The results obtained are the design of the nursing care documentation system and palliative screening. The nursing documentation system can be used for learning palliative nursing care and screening paiative patients using screening.